2020
DOI: 10.12659/msm.919272
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Potent Multi-miRNA Signature for Prediction of Prognosis of Osteosarcoma Patients

Abstract: Departmental sources Background: Osteosarcoma, the most common solid malignancy, has high incidence and mortality rates. We constructed a miRNA-based signature that can be used to assess the prognosis of osteosarcoma patients. Material/Methods: The miRNA profile was derived from the Gene Expression Omnibus (GEO) website, with matched clinical records. The miRNA-based overall survival (OS)-predicting signature was established by LASSO Cox regression analysis. Receiver operating characteristic (ROC) curve and Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…MiR‐591 also functioned as a tumor suppressor 25,26 . Our research data revealed that miR‐591 was downregulated in OS, consistent with the results reported by Luo et al 27 It was also the first demonstration that overexpression of miR‐591 could impede OS development by promoting apoptosis and autophagy, and inhibiting proliferation, migration and invasion of OS cells. Meanwhile, silencing circABCC1 inhibited OS cell malignancy, which were rescued by suppressing miR‐591 expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MiR‐591 also functioned as a tumor suppressor 25,26 . Our research data revealed that miR‐591 was downregulated in OS, consistent with the results reported by Luo et al 27 It was also the first demonstration that overexpression of miR‐591 could impede OS development by promoting apoptosis and autophagy, and inhibiting proliferation, migration and invasion of OS cells. Meanwhile, silencing circABCC1 inhibited OS cell malignancy, which were rescued by suppressing miR‐591 expression.…”
Section: Discussionsupporting
confidence: 91%
“…24 MiR-591 also functioned as a tumor suppressor. 25,26 Our research data revealed that miR-591 was downregulated in OS, consistent with the results reported by Luo et al 27 It was also the first demonstration that overexpression of miR-591 could impede OS Histones serve a key part in cancer development and are expected to be a novel strategy in cancer treatment. 28 It has been reported that histone deacetylase 4 (HDAC4) is highly expressed in osteosarcoma, 29 which can be involved in the development of osteosarcoma by regulating cellular behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, there is a need to develop and study prognostic models of osteosarcoma to guide targeted therapy. With the development of bioinformatics and sequencing technology, many scholars have constructed different prognostic models of osteosarcoma to analyze the characteristics of the disease (28)(29)(30). However, most of the parameters used to construct prognostic models consider only the genome or transcriptome and do not consider biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, there are several gene expression-based signatures for the prognosis of osteosarcoma [34][35][36][37][38][39][40]. Moreover, gene signatures based on cell death have been reported in diverse cancers, such as lung cancer, hepatocellular carcinoma and gastric cancer [32,33,41].…”
Section: Discussionmentioning
confidence: 99%